Exploring slow fashion consumer buying behavior in the context of sustainability: a systematic literature review using TCCM approach - Pappu Sindhuja; V. V. Devi Prasad Kotni; Aervina Misron; Halimaton Hakimi; Sai Deepti Udandrao (Cogent Business & Management, 2025)
Growing environmental concerns have led to much research on the ethical shift in how people shop. Consumer attitudes toward sustainable products have emerged, though consumers prefer them, and actual purchases remain minimal, showing the existence of the attitude-behavior gap. The mixed findings of the current studies demand this review of existing research work that has been discussed in the sustainable clothing domain for better understanding. This study delves into the current state of sustainable fashion research, encompassing theoretical frameworks, socio-demographic factors, geographical contexts, and product categories that have been extensively researched using the TCCM framework. This study systematically searched, selected, and synthesized relevant data to provide a rich literature map. This allows for critically appraising theoretical foundations, contextual factors, and the methodologies used in the previously conducted studies. The research indicates the dominance of specific theories in the available studies, suggesting a broader theoretical framework is needed. The study also brings to light underexplored product categories, socio-demographic segments, and geographic regions essential for marketers seeking to tap into untapped consumer niches. The research also identifies some factors influencing sustainable clothing purchases, hence implying further research into the same factors to develop more effective marketing strategies.